Development of auto re-closer earth leakage circuit breaker (AR-ELCB) - Shahful Bakhtiar, Shahiran (2009)
An Earth Leakage Circuit Breaker (ELCB) is an electrical device that disconnects protected circuit whenever it detects unbalance current between the phase conductor and the neutral conductor. Such an unbalance is sometimes caused by current leakage through the body of a person who is grounded when accidentally touching the energized part of the circuit. A lethal shock can result from these conditions. ELCB are designed to disconnect this fault fast enough to mitigate the harm caused by such shocks. Currently, there is no Earth Leakage Circuit Breaker (ELCB) with auto re-closer features in the market. The current ELCB that available in the market is a manual type and cannot differentiate between temporary disturbances and permanent faults. It’s means that, if a disturbance or fault occurs on the protected area (house or shop), the protection system will force ELCB to trip. One of the drawbacks of the common ELCB is that, it’s can’t turn on the power supply back to the normal operation condition although only a short disturbance occurs. Such disturbance is lightning strike on the transmission line in the distribution site near to the protected area. To turn the power back to normal operation, consumers need to do that manually. To overcome this problem, Auto Re-closer Earth Leakage Circuit Breaker (AR-ELCB) has been developed. This thesis presents the development of AR-ELCB. This device was designed to differentiate between permanent fault and short disturbances (lightning).